ICT education through project-based learning in the Kurikulum Merdeka - Muhamad Wahyu Darmawan (Himpunan Pengembang Kurikulum Indonesia, 2026)
This study examines the implementation of the Kurikulum Merdeka in Information and Communication Technology (ICT) learning in junior high schools. The implementation of curriculum reform in technology-based subjects is crucial for preparing students to face the demands of digital literacy and 21st-century skills. This study was conducted to identify how ICT learning is implemented within the Kurikulum Merdeka and to explore the challenges and solutions implemented in schools. A qualitative descriptive method was used, involving direct observation and structured interviews with ICT teachers, curriculum coordinators, and school librarians. The study findings revealed that Project-Based Learning (PjBL) is consistently implemented in ICT classes, despite limitations in digital media and infrastructure. Challenges faced include a lack of computer laboratories, limited internet access, and teachers' reluctance to adapt to new teaching models. To overcome these obstacles, schools held internal training sessions, held collaborative discussions among teachers, and utilized student-owned devices. This study concluded that despite infrastructure limitations, the implementation of the Kurikulum Merdeka has a positive impact on students' digital skills and critical thinking. This research provides practical insights for schools, educators, and policymakers in optimizing curriculum reform in ICT subjects. Abstrak Penelitian ini mengkaji penerapan Kurikulum Merdeka dalam pembelajaran Teknologi Informasi dan Komunikasi (TIK) di SMP. Penerapan reformasi kurikulum dalam mata pelajaran berbasis teknologi sangat penting untuk mempersiapkan murid menghadapi tuntutan literasi digital dan keterampilan abad ke-21. Penelitian ini dilakukan untuk mengidentifikasi bagaimana pembelajaran TIK dilaksanakan dalam Kurikulum Merdeka serta mengeksplorasi tantangan dan solusi yang diterapkan di sekolah. Metode deskriptif kualitatif digunakan, yang melibatkan pengamatan langsung dan wawancara terstruktur dengan guru TIK, koordinator kurikulum, dan pustakawan sekolah. Temuan penelitian mengungkapkan bahwa Project-Based Learning (PjBL) secara konsisten diterapkan di kelas TIK, meskipun didukung oleh penggunaan media digital dan menghadapi keterbatasan infrastruktur. Tantangan yang dihadapi meliputi kurangnya laboratorium komputer, keterbatasan akses internet, serta kurangnya adaptasi guru terhadap model pengajaran baru. Untuk mengatasi kendala tersebut, sekolah menyelenggarakan pelatihan internal, diskusi kolaboratif antar guru, serta memanfaatkan perangkat milik murid. Penelitian ini menyimpulkan bahwa meskipun terdapat keterbatasan infrastruktur, penerapan Kurikulum Merdeka berdampak positif terhadap keterampilan digital dan pemikiran kritis murid. Penelitian ini memberikan wawasan praktis bagi sekolah, pendidik, dan pembuat kebijakan dalam mengoptimalkan reformasi kurikulum pada mata pelajaran TIK. Kata Kunci: Kurikulum Merdeka; literasi digital; pembelajaran TIK; project-based learning